Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

aye4angela

  • 3 years ago

I think its substitution.. 3x - y = 1 x + y = 7

  • This Question is Closed
  1. apple_pi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Add the equations together: 3x - y + x + y = 1 + 7 4x = 8 x = 2 Now substitute x = 2 into whichever equation (2 is easier) 2 + y = 7 y = 5 So x = 2, y = 5

  2. aye4angela
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Ohkay that's what i got. ^-^ just wanted to make sure.

  3. apple_pi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Sure thing. If you want to make sure, just substitute your x and y into both equations and see if they work

  4. apple_pi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Oh yeah. You may want to close this question ;D

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy